Empowering Local Service Providers (LSP): Training on Mechanized Direct-Seeded Rice (DSR) for Precision Sowing - Ahmed, Sharif; Miajy, Abdullah; Haque, Abdul; Bhandari, Humnath (International Rice Research Institute, 2025)
In northern Bangladesh, the widespread adoption of mechanized Direct-Seeded Rice (DSR) remains slow due to limited access to suitable seeding machines and lack of skilled operators. These constraints prevent farmers from fully benefiting from climate-smart technologies, especially as they face the increasing challenges from labor shortages, rising input costs, and unpredictable rainfall patterns driven by climate change.